a Comparison Between Dexamethasone and Prednisolone in ARDS Patients: Literature Review - Aqil, Faiq Akhmad; Oktarlina, Rasmi Zakiah; Junando, Mirza; Pardilawati, Citra Yuliyanda (CV. Jasa Sukses Abadi, 2024)
During the COVID-19 pandemic, dexamethasone and methylprednisolone are used to treat COVID-19 patients, particularly those who have acute respiratory distress syndrome (ARDS). Numerous studies have demonstrated that dexamethasone significantly improves respiratory function and lowers mortality in COVID-19 patients, particularly those who need mechanical ventilation. Patients with ARDS with COVID-19 who received dexamethasone had fewer days alive and ventilator-free days, according to a randomized study like the CoDEX trial. But methylprednisolone has also demonstrated encouraging outcomes in treating severe COVID-19 pneumonia, particularly when used as a short-term treatment. The dosage and mode of administration of the two medications differ; dexamethasone is more frequently used to treat the systemic inflammation brought on by this viral infection.